Diffusion and molecular dynamics of lipo-fullerenes in phospholipid membranes studied by NMR and quasi-elastic neutron scattering - Hetzer, Michael; Karakatsanis, Paul; Casalta, Helene; Hirsch, Andreas; Camps, Xavier; Vostrowsky, Otto; Bayerl, Thomas (Journal of Physical Chemistry A, 2000)
Lipo-fullerenes are lipophilic C derivatives (six pairs of alkyl chains symmetrically grafted to the C cage) that intercalate in phospholipid bilayers by the formation of rodlike structures of nanoscopic dimensions. Proton NMR measurements in the fringe field of a superconducting magnet (SFF-NMR) were employed to measure the long-range self-diffusion of lipo-fullerenes intercalated in oriented multilayers of dipalmitoylphosphatidylcholine (DPPC) between 27 and 70 °C. The lipo-fullerene diffusion was found to be an order of magnitude slower than that of the DPPC in the host bilayer. The lipo-fullerene diffusion continued largely unaffected even under conditions when the host bilayer assumed a solidlike gel state, indicating a decoupling of lipo-fullerene and DPPC motion. Quasi-elastic neutron scattering (QENS) was used to study the molecular dynamics of the lipo-fullerenes within the bilayer at four energy resolutions of the spectrometer (1, 19, 62, and 500 μeV), covering selectively the gighertz to terahertz frequency range of molecular motion. We find that the molecular dynamics in this frequency range is dominated by the motion of the 12 alkyl chains attached to each C. At 25 °C where both the DPPC and the lipo-fullerenes are in a solidlike state, the dynamics of the latter is dominated by kink defects of the alkyl chains at high frequency (terahertz range) and alkyl chain jumps at lower frequency gighertz range). At 75 °C where both components are fluid, the lipo-fullerene dynamics can be described by a superposition of segmental rotational motion of chains and a spatially restricted diffusion of the chain inside a spherical volume. The radii of the volumes were found to scale linearly with the distance of the chain segment from the fullerene cage. © 2000 American Chemical Society.